Traditional Chinese Medicine as an Adjunctive Therapy Improves Cardiac Function and Reduces Serum Inflammatory Markers in Patients with Chronic Heart Failure: Traditional Chinese Medicine Enhances Cardiac Function in Heart Failure - Huang, Chunhui; Zhang, Wei; Shi, Yiping; Chen, Fangchao; Zhou, Jianru; Zheng, Yonghong (Journal of Medical Biochemistry, 2024)
Background: To analyze the effects of traditional Chinese medicine treatment compared to standard treatment in improving cardiac function and lowering serum biomarker levels in patients with chronic heart failure (CHF).Methods: A total of 40 CHF patients admitted to the Cardiology Department of our hospital from January 2021 to August 2023 were selected as the study subjects. They were divided into an observation group (treated with traditional Chinese medicine) and a control group (treated with Western medicine standard therapy) based on a random number table, with 20 cases in each group. The clinical efficacy, Minnesota Living with Heart Failure Questionnaire (MLHFQ) scores before and after treatment, 6-minute walk test (6MWT) results, cardiac output (CO), ejection fraction (EF), left ventricular end-diastolic pressure (LVEDP), serum high-sensitivity C-reactive protein (hs-CRP), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and N-terminal pro-brain natriuretic peptide (NT-proBNP) levels were observed and compared between the two groups. Adverse reaction rates were also recorded.Results: The total effective rate of the observation group was higher than that of the control group, and the intergroup comparison showed statistical differences (P < 0.05). Before treatment, there were no statistically significant differences in MLHFQ scores, 6MWT results, CO, EF, LVEDP, serum hs-CRP, IL-6, TNF-α, and NT-proBNP levels between the two groups (P > 0.05). However, after treatment, the MLHFQ scores, LVEDP, serum hs-CRP, IL-6, TNF-α, and NT-proBNP levels in the observation group were lower than those in the control group, while the 6MWT results, CO, and EF were higher than those in the control group, and the intergroup comparisons showed statistical differences (P < 0.05). The adverse reaction rate in the observation group was lower than that in the control group, and the intergroup comparison showed statistical differences (P < 0.05).Conclusions: Compared to standard treatment, traditional Chinese medicine treatment is more effective in improving cardiac function, enhancing exercise tolerance and quality of life, lowering serum inflammatory markers and NT-proBNP levels, and reducing the incidence of adverse reactions in patients with chronic heart failure.
Keywords: Chronic heart failure; Traditional Chinese medicine; cardiac function